Respiratory morbidity in Rett syndrome: an observational study - MacKay, J.; Leonard, H.; Wong, K.; Wilson, A.; Downs, Jennepher (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Mac Keith Press Aim: Respiratory illness is a major cause of morbidity and mortality in Rett syndrome. This study investigated respiratory morbidity and relationships with age, mutation type, feeding, and walking status. Method: Families registered with the InterRett database (n=399) provided data on the health of their child with Rett syndrome (age 2–57y). Hospital admissions because of lower respiratory tract infection (LRTI) over a 5-year exposure period were investigated by age, mutation type, enteral feeding, and walking status. Results: A hospital admission for LRTI over the previous 5 years was reported for slightly more than one-fifth (21.4%) of individuals. Age and mutation groups did not seem to influence hospital admissions for LRTI but there was nearly twice the risk of an admission with enteral feeding (adjusted relative risk 1.79, 95% confidence interval [CI] 1.21–2.65). Compared with independent walking, being unable to walk was associated with a sixfold increased risk (adjusted relative risk 6.73, 95% CI 3.42–13.25), with assisted walking associated with an intermediate risk. Interpretation: Beyond the influence of mutation type, walking seems to have protective effects on respiratory health. Further studies of exercise physiology in Rett syndrome and how this can be influenced by increasing activity levels are indicated. What this paper adds: Rett syndrome is associated with increased vulnerability to lower respiratory tract infection (LRTI) requiring hospitalization. Enteral feeding is associated with a higher risk of hospital admission for LRTI. Assisted walking mitigates the risk of hospital admission for LRTI for those unable to walk independently.